2016
DOI: 10.1001/jamaophthalmol.2016.1073
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Clinical Findings in Patients With Knobloch Syndrome

Abstract: IMPORTANCE Knobloch syndrome is a rare, recessively inherited disorder classically characterized by high myopia, retinal detachment, and occipital encephalocele, but it is now known to have an increasingly variable phenotype. There is a lack of reported electrophysiologic data, and some key clinical features have yet to be described.OBJECTIVE To expand on current clinical, electrophysiologic, and molecular genetic findings in Knobloch syndrome. DESIGN, SETTING, AND PARTICIPANTSTwelve patients from 7 families u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 45 publications
6
53
0
Order By: Relevance
“…Our patient presents with early onset high myopia and other characteristic eye findings of KS, along with a focal occipital alopecic lesion (OAL). Diffuse chorioretinal atrophy and abnormal vitreous condensations like hers have been described as key features of vitreoretinal degeneration (Hull et al, 2016). Variable presentations include abnormalities of the anterior segment and an asymmetric involvement of eye globes (Corbett et al, 2017;Hull et al, 2016), both of which are also observed in our patient.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Our patient presents with early onset high myopia and other characteristic eye findings of KS, along with a focal occipital alopecic lesion (OAL). Diffuse chorioretinal atrophy and abnormal vitreous condensations like hers have been described as key features of vitreoretinal degeneration (Hull et al, 2016). Variable presentations include abnormalities of the anterior segment and an asymmetric involvement of eye globes (Corbett et al, 2017;Hull et al, 2016), both of which are also observed in our patient.…”
Section: Discussionsupporting
confidence: 59%
“…Diffuse chorioretinal atrophy and abnormal vitreous condensations like hers have been described as key features of vitreoretinal degeneration (Hull et al, 2016). Variable presentations include abnormalities of the anterior segment and an asymmetric involvement of eye globes (Corbett et al, 2017;Hull et al, 2016), both of which are also observed in our patient. High myopia usually presents in infancy as nystagmus and/or strabismus and can eventually lead to a collapsed abnormal vitreous, glaucoma, ectopia and retinal detachment during childhood.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Additional ocular manifestations include white fibrillar vitreous condensation, diffuse severe vitreoretinal atrophy, persistent fetal vasculature, distinct macular atrophy, cone-rod dysfunction, electroretinogram diminution, retinal pigment epithelial atrophy, prominent choroidal vessels, smooth (cryptless) irides, zonular weakness with temporal lens subluxation, pigment dispersion syndrome and associated glaucoma, and some degree of cataract. 2 Neurologic deficits include epilepsy, developmental delay, and midline cranial defects. Occipital defects may range from bony defects to an encephalocele.…”
Section: Introductionmentioning
confidence: 99%